2013
DOI: 10.3390/molecules18033529
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia chebula Extract Protects OGD-R Induced PC12 Cell Death and Inhibits LPS Induced Microglia Activation

Abstract: Abstract:Terminalia chebula, native to Southeast Asia, is a popular medicinal plant in Ayurveda. It has been previously reported to have strong antioxidant and anti-inflammatory efficacy. In this study, we aimed to investigate if fruit extract from T. chebula might protect neuronal cells against ischemia and related diseases by reduction of oxidative damage and inflammation in rat pheochromocytoma cells (PC12) using in vitro oxygen-glucose deprivation followed by reoxygenation (OGD-R) ischemia and hydrogen per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Chebulagic acid and chebulinic acid are the major constituents and their chemical structures are shown in Figure 6. In experimental and human studies, TCE and its components have been shown to exert antioxidant, anti-inflammatory and analgesic activities, thereby exerting anti-arthritic effects [72][73][74][75][76][77][78][79][80][81][82]. Das et al [83] demonstrated that gallic acid in TCE inhibited NF-κB activity, suggesting its potential for anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Chebulagic acid and chebulinic acid are the major constituents and their chemical structures are shown in Figure 6. In experimental and human studies, TCE and its components have been shown to exert antioxidant, anti-inflammatory and analgesic activities, thereby exerting anti-arthritic effects [72][73][74][75][76][77][78][79][80][81][82]. Das et al [83] demonstrated that gallic acid in TCE inhibited NF-κB activity, suggesting its potential for anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…T. Chebula extract has protective effectsagainst in-vitro experiment where oxygen-glucose deprivation followed by reoxygenation (OGD-R) ischemia and hydrogen peroxide (H2O2) induced cell death on PC12 cells. T. chebula extract showed the diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and reduced H2O2-induced MDA production where DPPH radical scavenging activity of T. chebula is mostly related to the hydroxyl group in ellagic acid [91]. Moreover, Ellagitannins produces hexa-hydroxydiphenic acid (HHDP) on ester bonds hydrolysis with acids or bases, which rearranges spontaneously to produce Ellagic acid [45] .…”
Section: Ellagic Acid and Amyloid Beta (Aβ) Peptidementioning
confidence: 99%
“…The activation of the primary microglia is one of the major reasons of cellular inflammation in ischemic condition. Terminalia chebula extract reduced LPS induced cell death and inhibited the production of NO by BV2 cellsin Lipopolysaccharide activated microglia cells (BV2 cell) and reduce cellular inflammation [91] . Pomegranates extract feeding improved behavioral performance in APP/PS1 mice, which correlated with decreased microgliosis, nuclear factor of activated T-cell c2 (NFATc2) activity, and brain TNF-α concentration.…”
Section: Ellagic Acid and Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is a robust and validated model for preliminary screening of neuroprotective agents. [150][151][152] Plant-derived flavonoids belong to the broader class of polyphenolic compounds, which are purported to have salutary effects in various disease states. 153 What makes flavonoids a fascinating class of molecules is that, in addition to their chemical diversity and abundance in natural sources, their pharmacological effects are also multi-faceted.…”
mentioning
confidence: 99%